The Role of Principal's Pedagogical Leadership in Teacher Professional Development at SMKS 6 Muhammadiyah Lebong Utara - Valerian Valerian; Adi Asmara (CV. Bimbingan Belajar Assyfa, 2026)
The principal's pedagogical leadership is a strategic factor in teacher professional development and improving the quality of education. This article discusses the concept of pedagogical leadership, its role in teacher professional development, implementation strategies, challenges faced, and its implications for improving the quality of education at SMKS 6 Muhammadiyah Lebong Utara. This study uses a qualitative method in the form of a case study involving the principal, teachers, and educational staff as participants. Data were collected through structured interviews, observations, and document studies, then analyzed using the Miles and Huberman framework. The results show that the principal's pedagogical leadership plays a central role in teacher professional development through five main functions: as an academic vision formulator, academic supervisor, facilitator of teacher professional learning, builder of a school culture that supports continuous learning, and as a motivator and role model. Effective implementation strategies include data-based needs mapping, sustainable academic supervision, formation of professional learning communities, management of resources that support learning, and continuous evaluation. Challenges faced include the principal's administrative burden, teacher resistance to change, resource limitations, and mismatches between training programs and teacher needs. This study concludes that teacher professional development will be more effective when the principal implements systematic, sustainable pedagogical leadership based on teachers' actual needs. The implication is that strengthening the principal's pedagogical leadership needs to become a priority agenda in education policy, not only in administrative and managerial aspects, but also in academic supervision competence, facilitation of learning communities, learning data analysis, and instructional change leadership.